Reordering of Test Vectors Using Weighting Factor Based on Average Power for Test Power Minimization - Vidhyia, M.; K. Paramasivam; S. Elayaraja; S. Bharathiraja (Asian Journal of Electrical Sciences, 2015)
Power consumption is one of the biggest challenges in high performance VLSI design and testing. Low power VLSI circuits dissipate more power during testing when compared with that of normal operation. Dynamic power has been the dominant part of power dissipation in CMOS circuits; however, in future technologies the static portion of power dissipation will outreach the dynamic portion. The proposed approach is based on a reordering of test vectors in the test sequence to minimize the switching activity of the circuit using test application. In this paper weighted switching activity is derived based on the average power consumed in the logic gates during all possible event conditions. Since this weighted switching activity is based on the power, which gives more accurate results. The proposed algorithm is implemented and verified using ISCAS85 benchmark circuits. Power is estimated for the circuits using Tanner EDA tool. The results show that power is reduced significantly over the existing methods